Do sex and gender aspects influence non-adherence to secondary prevention measures after myocardial infarction? - Guillermo Moreno; Lourdes Vicent; Nicolás Rosillo; Juan Delgado; Enrique Pacheco Del Cerro; Héctor Bueno (Elsevier, 2024)
Objective: This study aimed to determine the prevalence of non-adherence to preventive interventions, its clinical consequences, and factors associated with non-adherence to secondary prevention measures, with a special emphasis on sex and gender. Methods: Prospective observational study of patients hospitalized for acute myocardial infarction (AMI) in whom an evaluation of adherence to medication, Mediterranean diet, physical activity, and cardiac rehabilitation was performed after 6 and 12 months, with systematic assessment of predictors including patient-, disease-, psychological-, social-, and gender-related factors using self-administered questionnaires. Results: Of 503 patients included, 101 (20,1%) were females. At one year, 85% of patients did not adhere to at least one of the recommendations with no differences between females and males. However, two factors more frequent in females, caregiver burden (adjusted OR, 1.45; 95%CI, 1.08-1.94) and depressive symptoms (adjusted OR, 1.40; 95%CI, 1.03-1.92) predicted non-adherence to all measures together. Chronic kidney disease (aOR, 3.24; 95%CI, 1.02-10.48) and being female (aOR, 2.21; 95%CI, 1.18-4.13) were associated with non-adherence to the Mediterranean diet; diabetes with organ damage (aOR, 12.06; 95%CI, 1.93-7.69) and older age (aOR, 0.96 per year; 95%CI, 0.93-0.99), among others, with physical activity; and higher body mass index with cardiac rehabilitation participation (aOR, 1.07; 95%CI, 1.002-1.14) and completion (aOR, 1.14; 95%CI, 1.03-1.26) Conclusion: Adherence to all secondary prevention measures after AMI remains very low and is associated with several gender-related factors. Multidisciplinary intervention strategies targeting the most vulnerable patient groups, such as females or patients with diabetes, obesity, chronic kidney disease, or depression, are warranted.